Crossed fused renal ectopia: Challenges in diagnosis and management - Shailesh Solanki; Veereshwar Bhatnagar; Arun K Gupta; Rakesh Kumar (Wolters Kluwer Medknow Publications, 2013)
Aim: Crossed fused renal ectopia is a rare congenital malformation, which is reported to be usually asymptomatic but may have varied presentations. This survey was conducted to study the clinical profile and the challenges posed in the management of this entity. Materials and Methods: Retrospective analysis of 6 patients diagnosed to have crossed fused renal ectopia during 1997-2010. The diagnosis was confirmed during surgical exploration in one patient. In one patient it was detected on antenatal ultrasonography and in the other 4 patients it was detected during investigations for abdominal pain, abdominal mass, anorectal malformation and urinary tract infection. Results: The left moiety was crossed and fused with the right moiety in 4 cases. Ultrasonography was found to be a good screening investigation with useful diagnostic contributions from CT scans, radionuclide scintigraphy and magnetic resonance urography. Micturating cystourethrography revealed presence of VUR in 4 cases, 3 of whom have undergone ureteric reimplantation. Two patients required pyeloplasty for pelviureteric junction obstruction; in one of these patients the upper ureter was entrapped in the isthmus. In one patient, a non-functioning moiety resulted in nephrectomy. All children were asymptomatic at last follow-up with stable renal functions. Conclusions: Crossed fused renal ectopia was detected in most patients during investigation for other problems. It was found more commonly in boys. The left moiety was crossed to the right in the majority of cases. Associated urological problems were found in most cases and required the appropriate surgical management.